1992
DOI: 10.1111/j.1151-2916.1992.tb07869.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reoxidation on the Grain‐Boundary Acceptor‐State Density of Reduced BaTiO3 Ceramics

Abstract: KaohsiungTo investigate the effect of reoxidation on the grainboundary acceptor-state density of reduced barium titanate, n-doped BaTiOa ceramics are sintered in a reducing atmosphere (2% H2 + 98% N2) and then annealed in oxygen.After annealing at 1150°C for different times, the experimental results show a relationship between temperatureaveraged acceptor-state density and annealing time as N, = N,,Bt'/" with n between 2 and 3. An inherent acceptorstate density N,, = 4.25 X 10" cm-' is obtained with an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 11 publications
3
18
1
Order By: Relevance
“…This figure shows that the PTCR effect of samples B and C is higher than that of sample A primarily because of the oxidation at grain boundaries owing to the chemisorbed oxygen during sintering [27][28][29][30]. This observation strongly supports the validity of the Heywang model as an explanation of the PTCR effect in BaTiO 3 ceramics [13][14][15]. Fig.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This figure shows that the PTCR effect of samples B and C is higher than that of sample A primarily because of the oxidation at grain boundaries owing to the chemisorbed oxygen during sintering [27][28][29][30]. This observation strongly supports the validity of the Heywang model as an explanation of the PTCR effect in BaTiO 3 ceramics [13][14][15]. Fig.…”
Section: Resultssupporting
confidence: 81%
“…This behavior, known as the positive temperature coefficient of resistivity (PTCR) effect, has been substantially investigated owing to the applications of thermistor devices such as TV screens, computer monitors, self-regulated heaters, and current suppressors [11][12][13][14][15]. Theoretical models of the PTCR effect have been proposed by both Heywang [13][14][15] and Jonker [16]. Both theories and experiments reported that the effect is a grain-boundary related phenomenon [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such a reducing atmosphere resulted in a poor PTC effect or no PTC effect due to desorption of grain boundary oxygen [12]. In the present work, a mildly reducing atmosphere has been employed.…”
Section: Introductionmentioning
confidence: 98%